Relationships of the emotional intelligence, working environment and caring behavior among nurses in Sabah, Malaysia - Norkiah Arsat (2017)
This study aimed to examine the relationship between emotional intelligence, working environment and caring behaviours of nurses and to examine how emotional intelligence acts as a mediator in the relationship between working environment and caring behaviour among nurses in Sabah. This is a cross-sectional study survey method, quantitative research design. Through cluster and multistage sampling techniques, 3359 nurses from public hospitals and public health service in Sabah have completed a study instruments ''The 24 - item Caring Behaviours Inventory (CBl-24)", "Trait Emotional Intelligence Questionnaire - Short Form (TEIQue-SF) " and "Practice Environment Scale of the Nursing Work Index (PES - NWI) ". The results of the SEM-PLS analysis shows that the nurses working environment has significant effect on nurses emotional intelligence and nurses caring behaviour. Emotional intelligence has a significant effect on nurse caring behaviours. Emotional intelligence was found to act as a mediator in the relationship between nurses' working environment and nurses' caring behaviours. The limitations of the research were explained along with the suggestion of future research.